Physiological responses during interval training at relative to critical velocity intensity in young swimmers - Toubekis, A. G.; Vasilaki, A.; Douda, H.; Gourgoulis, V.; Tokmakidis, S. (Journal of Science and Medicine in Sport, 2011)
Objectives: The purpose of this study was to examine the physiological responses on three interval training sets performed at intensities relative to the critical velocity which was calculated from two different combinations of distances using a 2-parameter linear model. Methods: In a controlled repeated measures design, ten male well trained swimmers (age: 15.2 ± 1.2 years) swam 5 × 400-m, 10 × 200-m and 20 × 100-m on separate days with rest to swimming ratio 1:8, aiming to maintain the critical velocity calculated from distances of 50, 100, 200, 400-m (CV4) or 200, 400-m (CV200-400). Results: The sustained velocity on the 5 × 400-m was lower compared to CV4 and velocity on the 20 × 100-m was higher compared to CV200-400. The velocity on the 10 × 200-m was kept similar to both CV4 and CV200-400 (5 × 400-m: 1.27 ± 0.07 vs. CV4: 1.33 ± 0.09 m s-1, p < 0.05; 20 × 100-m: 1.32 ± 0.02 vs. CV200-400: 1.28 ± 0.09 m s-1, p < 0.05; 10 × 200-m: 1.30 ± 0.10 m s-1 vs. CV4 and CV200-400, p > 0.05). The blood lactate concentration increased after 1200 compared to 400-m (4.45 ± 0.23 vs. 5.82 ± 0.24 mmol l-1, p < 0.05) and was no different between sets (p > 0.05). Stroke rate and stroke length were not different between and within conditions (p > 0.05). Heart rate during the recovery periods was lower in the 5 × 400-m compared to 10 × 200-m and 20 × 100-m training set (p < 0.05). Conclusion: Interval swimming pace can be adjusted in relation to critical velocity calculated from distances of 200 and 400-m or from distance of 50, 100, 200, 400 m. When the distance of repetitions is increased from 100 to 200 and 400-m the velocity should be reduced by 2% to achieve similar metabolic responses.